Association of human papillomavirus (HPV) infection and potentially pathogenic vaginal microorganisms in women attending at primary care nursing gynecological consultation (Research, Society and Development, 2021)
To identify the incidence of human papillomavirus (HPV) with the presence of other microorganisms. This is a cross-sectional study composed of 128 women who were attended in the basic health units, between 2014 and 2018, to perform the Pap smear. The presence of papillomavirus was investigated using conventional PCR with primers MY09/11 and GP5 +/6+ (echo and endocervix cells) and the smear bacterioscopy of vaginal secretions was performed to identify the microorganisms. Statistical was performed using the square test, including a risk ratio or 95% confidence interval. HPV infection was identified in 48.4% (n = 62) women. Corynebacterium sp (39.8%) was the most prevalent microorganism, followed by Escherichia coli (21.1%), Staphylococcus aureus (14.0%), Gardnerella vaginalis (13.2%) and Candida albicans (7%), respectively. According to statistical analysis or HPV and the group of potentially pathogenic microorganisms had a significant association p